MENGUNGKAP PRAKTIK AKUNTANSI AKAD MUDHARABAH PADA PEMBIAYAAN SYARIAH PT BANK SULSELBAR SYARIAH MAKASSAR - Suriyadi Nur; Andi Ririn Oktaviani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The aim of this research was to uncover how the recognition, measurement, presentation and disclosure of accounting practices mudharabah sharia in Islamic finance at PT Sulselbar Bank Syariah Makassar. The data analysis method used in this research is qualitative descriptive analysis prefentif. Company data that supports research data collected then analyzed by describing the state of the object or describe real research. The results showed that in general the Bank has applied the accounting practices mudharabah in accordance with generally accepted accounting principles in Islamic banking Indonesia and in accordance with Statement of Financial Accounting Standards (PSAK) Nomor 105 but related to the implementation of the pillars and terms of financing is not fully in accordance with the National Sharia Board Fatwa such differences persentage funds provided to customers. Financing portion by using mudharabah still smaller than murabahah financing. This is influenced by the allocation of financing for working capital only, while the murabahah financing in addition to working capital investment and consumption